An optimized background regimen design to evaluate the contribution of levofloxacin to multidrug-resistant tuberculosis treatment regimens: study protocol for a randomized controlled trial. Issue 1 (December 2017) - Bouton, Tara; Phillips, Patrick; Mitnick, Carole; Peloquin, Charles; Eisenach, Kathleen; Patientia, Ramonde; Lecca, Leonid; Gotuzzo, Eduardo; Gandhi, Neel; Butler, Donna; Diacon, Andreas; Martel, Bruno; et al.
Abstract Background Current guidelines for treatment of multidrug-resistant tuberculosis (MDR-TB) are largely based on expert opinion and observational data. Fluoroquinolones remain an essential part of MDR-TB treatment, but the optimal dose of fluoroquinolones as part of the regimen has not been defined. Methods/design We designed a randomized, blinded, phase II trial in MDR-TB patients comparing across levofloxacin doses of 11, 14, 17 and 20 mg/kg/day, all within an optimized background regimen. We assess pharmacokinetics, efficacy, safety and tolerability of regimens containing each of these doses. The primary efficacy outcome is time to culture conversion over the first 6 months of treatment. The study aims to determine the area under the curve (AUC) of the levofloxacin serum concentration in the 24 hours after dosing divided by the minimal inhibitory concentration of the patient'sMycobacterium tuberculosis isolate that inhibits > 90% of organisms (AUC/MIC) that maximizes efficacy and the AUC that maximizes safety and tolerability in the context of an MDR-TB treatment regimen. Discussion Fluoroquinolones are an integral part of recommended MDR-TB regimens. Little is known about how to optimize dosing for efficacy while maintaining acceptable toxicity. This study will provide evidence to support revised dosing guidelines for the use of levofloxacin as part of combination regimens for treatment of MDR-TB. The novel methodology can be adapted to elucidate the effect of other single agents in multidrug antibiotic treatment regimens. Trial registration ClinicalTrials.gov, NCT01918397 . Registered on 5 August 2013.